Optimalisasi Fitrah Manusia sebagai Pendekatan Pedagogis Islam dalam Menangani Siswa Underachiever - Dimaz Andrean; Yusuf, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue of underachieving students represents an educational challenge marked by the disparity between students' intellectual capabilities and their academic accomplishments. Viewed through the lens of Islamic education, this state can be interpreted as the inadequate realization of human nature encompassing intellectual, emotional, spiritual, and social dimensions. This study intends to investigate the challenges faced by underperforming students and explore methods to enhance human potential using an Islamic educational framework. The study employs a qualitative method featuring a case study conducted at Ma'arif Sukorejo High School. Data was collected via observation, detailed interviews, and documentation, subsequently analyzed using the Miles and Huberman framework through the phases of data reduction, data display, and conclusion formulation. The study's findings indicate that the challenges faced by underachiever students are affected by internal factors such as low motivation to learn, a lack of self-confidence, procrastination habits, and poor self-control, along with external factors like insufficient family support, the impact of the social environment, and overuse of social media. The Islamic educational method is implemented via spiritual guidance, emotional strategies, conversational learning, enhancing character, and individual mentoring. The strategy to enhance human nature involves incorporating tawhid values into education, fostering a conducive learning atmosphere, encouraging muhasabah practices, bolstering intrinsic motivation stemming from spirituality, personalizing approaches, and promoting collaboration between educational institutions and families. The research finds that the Islamic educational method rooted in human nature can serve as a comprehensive solution in assisting struggling students to fully realize their academic, spiritual, emotional, and social capabilities.